RESEARCH ON SOME TECHNICAL FACTORS OF MANUFACTURING COMPOSITE FROM COIR FIBER AND WASTE TIRE CHIPS WITH UREA-FORMALDEHYDE RESIN AS A SUBSTRATE - Xuan Nien, Hoang; Minh Hung, Nguyen (Journal of Forestry Science and Technology, 2018)
The problem of using waste from the processing or reusing of waste materials has been established by many countries in the world for efficient utilization of resources and minimizing environmental pollution. Coconut coir fiber and Waste tire chips are two types of materials made from various natural and man-made scraps. However, by combining them with appropriate proportions, they will create a good substrate for the creation of composites as materials for the manufacture of furniture and building materials with the participation of substrate urea-formaldehyde (UF). This paper presents the results of research: Good bonding ability of the rubber specimens made from waste tires together with the adhesive of UF by hot press; and the correlation of temperature, compression time and amount of substrate to the quality of composite CCF and WTC. The results show that: Under the influence of technological factors: Temperature of 165oC; Compression pressure 1.85 MPa; Pressing time of 2.5 min/mm thickness; Adhesive UF 15%; The raw material ratio of reinforcement (by product volume) of Coconut coir fibers/Waste tire chips : 75/25, we can produce the composite material with the main properties: Density 0.525 g/cm3; Modulus of rupture 16.95 MPa; Internal bonding 0.67 MPa; Thickness swelling 1.16%. The physical-mechanical properties of composite Coconut coir fibers and Waste tire chips are higher than the requirements of common particleboard.